Studying glycobiology at the single-molecule level - Lakshminarayanan, A; Richard, M; Davis, B (Nature Research, 2018)
Attempts to elucidate the roles of carbohydrate-associated structures in biology have led to the distinct field of glycobiology research. The focus of this field has been in understanding the evolution, biosynthesis and interactions of glycans, both individually and as components of larger biomolecules. However, as most approaches for studying glycans (including mass spectrometry and various binding assays) use ensemble measurements, they lack the precision required to uncover the discrete roles of glycoconjugates, which are often heterogeneous, in biomolecular processes. Single-molecule techniques can examine individual events within challenging mixtures, and they are beginning to be applied to glycobiology. For example, single-molecule force spectroscopy (SMFS) by atomic force microscopy (AFM) has enabled the molecular interactions of sugars to be studied, single-molecule fluorescence microscopy and spectroscopy have led to insight into the role of sugars in biological processes and nanopores have revealed interactions between polysaccharides and their transporters. Thus, single-molecule technology is becoming a valuable tool in glycoscience.